Experimental quantum error detection - Jin, X; Yi, Z; Yang, B; Zhou, F; Yang, T; Peng, C (Springer Nature, 2012)
Faithful transmission of quantum information is a crucial ingredient in quantum communication networks. To overcome the unavoidable decoherence in a noisy channel, to date, many efforts have been made to transmit one state by consuming large numbers of time-synchronized ancilla states. However, such huge demands of quantum resources are hard to meet with current technology and this restricts practical applications. Here we experimentally demonstrate quantum error detection, an economical approach to reliably protecting a qubit against bit-flip errors. Arbitrary unknown polarization states of single photons and entangled photons are converted into time bins deterministically via a modified Franson interferometer. Noise arising in both 10 m and 0.8 km fiber, which induces associated errors on the reference frame of time bins, is filtered when photons are detected. The demonstrated resource efficiency and state independence make this protocol a promising candidate for implementing a real-world quantum communication network.